Multilevel Approach In Organizational Research: A Review Of Dual-Level Transformational Leadership - Pourbarkhordari, Amin; Zhou, Er Hua (Iris); Pourkarimi, Javad (European Scientific Journal, ESJ, 2016)
Due to the nature of organizations as hierarchically nested systems, multilevel theoretical models are relevant to the vast majority of organizational phenomena; hence, the main purpose of this review was clarifying the importance of conceptualization and testing theories at multiple levels of analysis. By doing this, the current study added to the gloom by providing a comprehension literature review with explicit consideration of multilevel directed theory and measures in organizational studies. Specifically, this review answered call for deliberate distinction between individual and group levels of analysis in leadership research, in particular transformational leadership (TFL) which in recent years, based on well-grounded theory stating to multiple levels is scarce. Our multilevel approach in examining organizational phenomena at different levels corroborates the recommendation to investigate the impact of constructs and their relationships at multiple levels of analysis. Finally, two prominent measurement models which have been conducted to exhibit dual level transformational leadership behaviors were recommended.